Pengaruh Komunikasi Pemasaran dan Price Discount terhadap Pengambilan Keputusan Pembelian Produk Oriflame - Ana, Nur; Rijal, Syamsu; Mustari, Mustari; Dinar, Muhammad; Hasan, Muhammad (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the effect of marketing communications and price discounts on the purchasing decisions of economic education students, Faculty of Economics and Business, Makassar State University for oriflame products. The population of this research is economic education students, Faculty of Economics, State University of Makassar, 2015-2021, and a sample of 61 students who are consumers of Oriflame. Data were collected by questionnaire. Data were analyzed by quantitative descriptive and multiple linear regression. The results showed that (1) marketing communication had a positive and significant effect on purchasing decisions for Oriflame products, (2) price discounts had a positive and significant effect on purchasing decisions for Oriflame products, (3) marketing communications and price discounts together had a positive and significant effect on Oriflame product purchasing decisions.